Genotypic Diversity among Salmonella Typhi Isolated from Children Living in Informal Settlements in Nairobi, Kenya - Mutile Kavai, Susan; Oyugi, Julius; Mbae, Cecilia; Wairimu, Celestine; Kering, Kelvin; Kebenei, Collins; Muturi, Peter; Omulo, Sylvia; Kariuki, Samuel (International Journal of Clinical Microbiology, 2024)
The persistence of multidrug-resistant (MDR) Salmonella Typhi (S. Typhi) is a challenge especially in regions where typhoid is endemic. Surveillance of circulating genotypes of MDR S. Typhi is crucial in typhoid acute cases and carriers. This study aimed to investigate genotypic diversity of S. Typhi from symptomatic and asymptomatic children in endemic settings in Nairobi, Kenya. Symptomatic and asymptomatic individuals’ ≤ 16 years were recruited at four health facilities and tested for typhoid through stool cultures. The S. Typhi isolates were subjected to antibiotic susceptibility testing to investigate multidrug resistance. The MDR S. Typhi isolates’ DNA was extracted and illumina sequenced. Raw reads were de novo assembled and analyzed by pathogen-watch. From the 90 sequenced isolates, 60 (67%) were confirmed to be S. Typhi (sequence Type 1 and genotype 4.3.1). Out of the 60 S. Typhi strains; 39 (65%) had plasmids, from these 38 (97%) had IncHI1 plasmids alone. Out of the 60, 59 (98%) S. Typhi isolates had blaTEM-1D. Point mutations conferring reduced susceptibility to quinolones were detected in 42 (70%) of S. Typhi isolates, from these; 14 (33%) had gyrA S83Y , and 28 (67%) gyrB S464F genes, respectively. This study reports 4.3.1 (H58) as the most dominant S. Typhi genotype responsible for spread of MDR phenotypes carried on IncHI1 plasmids. Presence of MDR S. Typhi with resistance genes such as blaTEM-1Dand reduced susceptibility to ciprofloxacin especially among asymptomatic individuals, reiterates the need for use of typhoid conjugate vaccine among vulnerable children as a control and prevention measure against typhoid.
Keywords: Salmonella Typhi; Genotypic Diversity; Informal Settlements; Multidrug Resistance; Typhoid